KOMUNIKASI DALAM PEMBELAJARAN TEMATIK KELAS VB MIN 1 KOTA PARIAMAN - Zulvia Trinova; Zulfahmi H B; Wahyuni Hamidah (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2020)
This research based on problem that we found in Madrash Ibtidaiyah Negeri I Grade V (Five) B in Pariaman City. There were 15 out of 22 students is passive and rarely communicate during learning. We know that communication is essential activity to make learning more active. The goal of this research is to describe: 1) what kind of communication between teacher and students during learning; 2) learning activity; 3) why student rarely communicate during learning. This research used descriptive qualitative methods. The subject of this research are 22 students and their teacher in Islamic Elementary School I Grade VB in Pariaman City. The data were collected through observation, interview, and document. The result of this research were: 1) there are three kind of communication conducted Madrash Ibtidaiyah Negeri I Grade VB in Pariaman City, those are: one way, two ways, and many ways communication; 2) during learning activity, the teacher more active than the student and most of the student are passive and rarely communicate. In other words, the learning activity focus on teacher; 3) students do not really like some of the course with specific reason in thematic learning